Preparation of colloidal carbon nanotube dispersions and their characterisation using a disc centrifuge - Nadler, Michael; Mahrholz, Thorsten; Riedel, Ulrich; Schilde, Carsten; Kwade, Arno (Carbon (New York), 2008)
After their synthesis, carbon nanotubes are usually obtained as mechanically entangled solid bodies or subsequently associate themselves into aggregates. This leads to the demand of an effective dispersing method for the preparation of CNT-based composites. This paper studies selected dispersing mechanisms such as cavitation and high shear forces for the preparation of colloidal CNT/epoxy dispersions, which were subject to a particle size analysis using a differential sedimentation based disc centrifuge. Due to the remarkable shape of carbon nanotubes the measurement routines had to be adjusted and a validation of measurement results was performed. The fact that the disc centrifuge is suitable for the detection of residual agglomerates in CNT dispersions was shown by monitoring the dispersing methods ultrasonication and calendering.